An investigation of the oncogenic potential and function of the dual specificity phosphatase 12 - Cain, Erica L. (Kansas State University, 2013)
Large-scale genomic approaches have demonstrated many atypical dual specificity phosphatases (DUSPs) are differentially expressed or mutated in cancer. DUSPs are proteins predicted to have the ability to dephosphorylate Ser/Thr and Tyr residues, and the atypical DUSP subgroup contains at least 16 members with diverse substrates that include proteins, nucleic acids, and sugars, and some of the atypical DUSPs function in the cell not as phosphatases but as scaffolds in signal transduction pathways. Of the atypical DUSPs, DUSP12 is one of the most evolutionarily conserved with homologs found in organisms ranging from yeast to humans. DUSP12 is of particular interest as it has been identified to be one of only two candidate genes for the target of a genetic amplification found in liposarcomas. Furthermore, DUSP12 may be an oncogene in that over-expression of dusp12 in cell culture promotes apoptosis resistance, cell motility, and the up-regulation of two established oncogenes, the hepatocyte growth factor receptor (c-met) and integrin alpha 1 (itga1). Additionally, DUSP12 may protect from apoptosis by functioning as a regulator of stress-induced translation repression and stress granule formation that may be due to its interaction with the DEAD Box RNA Helicase, DDX3.
Keywords: DUSP12; YVH1; Atypical DUSP; Cancer; Oncogene; Dual specificity phosphatase; Cellular Biology (0379)